2017
DOI: 10.1038/npp.2017.19
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Ketamine Attenuates Learned Fear

Abstract: Ketamine has been reported to be an efficacious antidepressant for major depressive disorder and posttraumatic stress disorder. Most recently, ketamine has also been shown to be prophylactic against stress-induced depressive-like behavior in mice. It remains unknown, however, when ketamine should be administered relative to a stressor in order to maximize its antidepressant and/or prophylactic effects. Moreover, it is unknown whether ketamine can be prophylactic against subsequent stressors. We systematically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 75 publications
3
68
3
Order By: Relevance
“…Here, we did not find that (R,S)-ketamine and (2R,6R)-HNK were antidepressant in female mice. However, we do not believe these results contradict previous findings (24)(25)42). Instead, differences in mouse strain and drug dosing likely contributed to the discrepancies that we have demonstrated.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Here, we did not find that (R,S)-ketamine and (2R,6R)-HNK were antidepressant in female mice. However, we do not believe these results contradict previous findings (24)(25)42). Instead, differences in mouse strain and drug dosing likely contributed to the discrepancies that we have demonstrated.…”
Section: Discussioncontrasting
confidence: 99%
“…We have recently shown that a single injection of (R,S)-ketamine given 1 week prior to CFC can attenuate learned fear in male mice (25) The FST is a behavioral assay that is broadly considered to have predictive validity when quantifying antidepressant efficacy (28). On day 1 of the FST, immobility time was comparable between saline and (R,S)-ketamine mice (30 mg/kg) ( Figure S01D).…”
Section: (2r6r)-hnk and (2s6s)-hnk Protect Against Distinct Stress-mentioning
confidence: 96%
See 3 more Smart Citations